2012
DOI: 10.1103/physrevx.2.021011
|View full text |Cite
|
Sign up to set email alerts
|

Precision Spectral Manipulation: A Demonstration Using a Coherent Optical Memory

Abstract: The ability to coherently spectrally manipulate quantum information has the potential to improve qubit rates across quantum channels and find applications in optical quantum computing. In this paper, we present experiments that use a multielement solenoid combined with the three-level gradient echo memory scheme to perform precision spectral manipulation of optical pulses. These operations include separate bandwidth and frequency manipulation with precision down to tens of kHz, spectral filtering of up to thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Compressing and stretching quantum optical pulses is potentially useful for increasing quantum data rates and matching bandwidths of photons to those of quantum memories [8,11,29]. An AFC memory is well suited for this task since it can be tailored to feature almost arbitrary chromatic dispersion, i.e.…”
Section: Pulse Compressing and Stretchingmentioning
confidence: 99%
See 2 more Smart Citations
“…Compressing and stretching quantum optical pulses is potentially useful for increasing quantum data rates and matching bandwidths of photons to those of quantum memories [8,11,29]. An AFC memory is well suited for this task since it can be tailored to feature almost arbitrary chromatic dispersion, i.e.…”
Section: Pulse Compressing and Stretchingmentioning
confidence: 99%
“…Combining storage and manipulation in a light-matter interface that can be integrated on-chip with other photonic components reduces the complexity and thus facilitates the development of future quantum technologies [2,[5][6][7]. To date there have only been a few investigations that employ a quantum storage device for coherent optical pulse manipulation [8][9][10][11][12]. However, these demonstrations feature various intrinsic limitations that impact future use in practical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GEM has also been applied to show various coherent manipulations. Since the frequency content of the light is stored spatially along the length of the ensemble, it lends itself to spectral manipulation of the stored light [67]. These experiments showed that it is possible to frequency-shift the recalled light and multiplex different frequencies of light at both the storage and recall stages of the experiment.…”
Section: Gradient Echo Memorymentioning
confidence: 93%
“…An alternative for realising Bragg scattering of spin waves is through the use of a controlled inhomogeneous broadening, and a prominant technique is the gradient echo memory (GEM) [18,19]. GEM was already shown to allow light storage at the quantum level with two [16] and three atomic levels [20], to demonstrate efficient pulse re-ordering [21] and spectral manipulation of light pulses that have large time-bandwidth products [22]. Here, we demonstrate that GEM can be used in conjunction with a grating to enable efficient coherent mapping between diffracted modes and propagating light fields.…”
mentioning
confidence: 99%